ANALISIS PEMEROLEHAN BAHASA INDONESIA PADA BAHASA PERTAMA DAN KEDUA ANAK USIA 5-6 TAHUN DI PAUD GENDIS KELURAHAN SARI REJO MEDAN POLONIA - Siregar, Nurul Arafah; Kartolo, Rahmat (Jurnal Bahastra, 2022)
This study analyzed the acquisition of Indonesian in the first and second languages of children aged 5-6 years in Paud Gendis, Sari Rejo Village, Medan Polonia. The problem discussed in this study is that there is a student at PAUD Gendis who is aged from 5-6 years old who still uses the first language in interacting and communicating with his friends and teachers. This can refer to several factors that make children still use their first language so that children have difficulty in learning the acquisition of their second language. The object of study is the field of phonology. The data presentation technique carried out, the researcher used a descriptive pattern. Researchers used a diary of how children speak in interacting with their teachers or friends and used video tape as a substitute for notebooks. Next is to take each utterance and describe the context. This research was conducted using a method of listening to the use of language. The basic technique of this method is in the form of tapping technique and is followed by advanced techniques in the form of free listening and note-taking techniques. As a result of the analysis of the 16 children, there were 7 children who made a lot of laryngal or hamzah sounds in sentences ending in the vowels /a/, /i/, and /u/. not only that, there were 7 children who experienced phonological changes resulting in sound changes such as the phoneme /r/ to /l/, /d/ to /t/ and /n/ to /m/. in this case, 7 children who are already 5-6 years old are classified as unnatural, because the child's age can already obtain a second language or be perfect in the mention and sound of the language used by the child. This greatly makes the child later have difficulty in speaking opponents because it is still difficult to understand the meaning of the child's language.